ANALISIS KESESUAIAN BUKU ‘MUHADASATI’ BERDASARKAN PRINSIP-PRINSIP LINGUISTIK DAN PENDIDIKAN MENURUT NASSER ABDULLAH AL-GHALI - Mujibur Rohman; Halimi Zuhdy; Idrus Muchsin Bin Agil (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the compatibility of the "muhadasati" textbook in teaching Arabic to non-native speakers based on the principles of material development proposed by Nasser Abdullah Al-Ghali. The "muhadasati" book, designed for beginners, emphasizes speaking skills using Modern Standard Arabic. This research uses a qualitative approach with content analysis methods, examining the alignment of the book with necessary language aspects such as phonology, grammar, and vocabulary. The findings indicate that although the book meets several criteria proposed by Al-Ghali, such as using Modern Arabic and introducing relevant vocabulary, there are some shortcomings, particularly in the areas of phonology teaching and the absence of a glossary. The study concludes that while the book is effective in practicing speaking skills, several areas need improvement to enhance the quality of Arabic language learning.